2010
DOI: 10.1007/s12350-010-9235-1
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue volume and coronary artery calcium to predict myocardial ischemia on positron emission tomography-computed tomography studies

Abstract: In this study, EAT volume assessed by CT was an independent predictor of ischemia on PET, and outperformed CAC score in a CAD naïve population at intermediate pre-test probability of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 26 publications
3
38
0
1
Order By: Relevance
“…In addition to being associated with coronary atherosclerosis, EAT has also been associated with myocardial ischemia. A study by Janik and colleagues showed that, in a small cohort of 45 patients, EAT thickness was associated with ischemia by 82 Rb PET and outperformed the CAC score as a predictor of ischemia [20]. Consistent with this, Tamarappoo et al reported that cardiac adipose tissue was predictive of myocardial ischemia on SPECT and enhanced diagnostic performance when added to the CAC score [30].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition to being associated with coronary atherosclerosis, EAT has also been associated with myocardial ischemia. A study by Janik and colleagues showed that, in a small cohort of 45 patients, EAT thickness was associated with ischemia by 82 Rb PET and outperformed the CAC score as a predictor of ischemia [20]. Consistent with this, Tamarappoo et al reported that cardiac adipose tissue was predictive of myocardial ischemia on SPECT and enhanced diagnostic performance when added to the CAC score [30].…”
Section: Discussionmentioning
confidence: 84%
“…However, although a high coronary atherosclerotic burden has been associated with decreased myocardial perfusion and the occurrence of ischemia, the CAC score is too imprecise for the prediction of myocardial ischemia [15,18,19]. Interestingly, previous studies have reported the incremental diagnostic value of cardiac adipose tissue above the CAC score for the detection of myocardial ischemia on 82 Rb positron emission tomography (PET) [20]. Similarly, in 92 symptomatic subjects, Nakazato et al demonstrated that EAT had incremental diagnostic value for the detection of hemodynamic significant CAD, as reflected by the concurrent presence of CAD on ICA and myocardial ischemia on 82 Rb PET, above conventional risk factors and the CAC score [21].…”
Section: Introductionmentioning
confidence: 99%
“…24 Therefore, because EAT is an important source of several proinflammatory and proatherogenic cytokines, EAT can have a direct effect on coronary atherosclerosis and/or cardiac structure and function. 4,25 Recently, several studies have recognized increased EAT as an independent determinant of the development and progression of coronary artery disease, 5,15 presence of myocardial perfusion abnormalities, 26 and vulnerable coronary atherosclerotic plaques. 7 EAT is a stronger determinant of coronary artery disease than visceral adiposity located in other body compartments.…”
Section: Discussionmentioning
confidence: 99%
“…EFV measurements by computed tomography (CT) have been shown to be predictive of myocardial ischemia by SPECT [12] and PET [13]. Several studies have investigated the prognostic value of EFV using non-contrast CT and cardiac CT angiography [7; 14-19].…”
Section: Introductionmentioning
confidence: 99%